“Anti-plagiarism” System in Self-regulation of Scientific Activity - N. I. Martishina (Высшее образование в России)
The article presents the author’s position in the discussions that have intensified at the present time about the “Anti-plagiarism” system. The article correlates the functions of the system “Antiplagiarism” with the problems of scientific activity in the post-nonclassical period of the development of science. The author supports the thesis that the use of this system, even in the presence of certain defects, in the existing conditions is an objective necessity. The article discusses the most frequently mentioned problems of using “Anti-plagiarism” and gives objections to certain criticisms. The author formulates the conditions for the effective application of the system in scientific and educational practice such as: 1) content analysis of textual coincidence in research papers only for reference purposes, 2) decision-making about the acceptance of manuscript for publication based on the general principles of publication and research ethics, 3) differential treatment of textual coincidence depending on the level, character, and genre of a paper, 4) unified standards for preparation of research publications and academic papers. The scientific community has to work out professionally oriented regulations for application of technical means of verification in various spheres of science and education.